Pengaruh Kompensasi terhadap Kinerja Pegawai Melalui Disiplin Kerja sebagai Variabel Mediasi: (Studi pada Pegawai PT. Pegadaian CPS Batu Biru Bangkalan) - Bayu Ariyadi; Indra Prasetyo; Chamariyah Chamariyah (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Bayu Ariyadi, 2025. The Influence of Compensation on Employee Performance through Work Discipline as a Mediating Variable: A Study on Employees at PT CPS Batu Pawnshop Blue Bangkalan. This explanatory study employs a quantitative research approach with a sample of respondents from PT CPS Batu Pawnshop in Blue Bangkalan. Data analysis is conducted using Smart PLS (Partial Least Squares) method. The objectives of the study are: 1) To examine and analyze the direct effect of compensation on employee performance at PT CPS Batu Pawnshop Blue Bangkalan; 2) To examine and analyze the direct effect of compensation on work discipline at PT CPS Batu Pawnshop Blue Bangkalan; 3) To examine and analyze the direct effect of work discipline on employee performance at PT CPS Batu Pawnshop Blue Bangkalan; 4) To examine and analyze the indirect effect of compensation on employee performance at PT CPS Batu Pawnshop Blue Bangkalan, mediated by work discipline. The results of the study show that: 1) The p-value for the compensation-performance relationship is 0.159, indicating that compensation has a positive but not significant effect on employee performance, as the significance value (0.159) is greater than 0.05; 2) The p-value for the compensation-discipline relationship is 0.005, indicating that compensation has a significant positive effect on work discipline, as the significance value (0.005) is less than 0.05; 3) The p-value for the discipline-performance relationship is 0.000, indicating that work discipline has a significant positive effect on employee performance; 4) The p-value for the compensation-discipline-performance relationship is 0.021, indicating that compensation has a significant positive effect on both work discipline and employee performance.